Preliminary Design of Kit Kinematics Learning Tools assisted by Phyphox Mobile Apps - Fatmawati, Intan; Sulisworo, Dwi (UNIVERISTAS PGRI MADIUN, 2021)
Integration of learning tools with information technology can enrich the learning experience, including in learning physics. This research is the development of kinematics learning tools assisted by Phypox to support the improvement of scientific thinking skills. The scope of kinematics material is horizontal straight motion, vertical straight motion, and circular motion. In this study, the initial design process and design evaluation were carried out. Evaluation of the initial design was carried out by five experts and data were collected using a questionnaire. Data analysis used Content Validity Ratio (CVR) and Content Validity Index (CVI). The analyzed aspects include six indicators, namely: the functional relationship between components, component completeness, work order, practicality, efficiency, and effectiveness. The results of this study indicate that the initial design of the kinematics learning device is in a good category (CVR = 5.60; CVI = 0.93). Thus, this learning tool can be further tested on relevant students. The impact of the use of this tool will not only increase science skills, with certain learning strategies it can also grow the skills of working together and critical thinking.